The Multi-Functional Modelling Shear Lag Method for Accurate Calculation of Static Response and Accordion Effect of Improved Composite Box Girders - Ya-Nan Gan; Zi-Chen Zhang; Gen-Hui Wang (The Baltic Journal of Road and Bridge Engineering)
The composite box girder with corrugated web and steel bottom plate (CW-SBS) is a kind of improved steel-concrete structures. The design of CW-SBS box girders needs the accurate method to calculate the working response and accordion effect in consideration of the self-stress equilibrium condition of shear lag warping stress and shear deformation. This study proposes the multi-functional modelling shear lag (MFMSL) method which adopts the four longitudinal displacement difference functions to model the variation of shear lag in the CW-SBS box girders with different wing slab widths and thicknesses. Therefore, MFMSL is a method to calculate the static response and accordion effect of the CW-SBS composite box girders. Structural differential equations based on the energy-variation principle present that the MFMSL method effectively improves the calculating accuracy of the CW-SBS box girder static response, which can be verified by both experimental and simulative results. Also, the MFMSL method demonstrates that the accordion effect of the CW-SBS box girder is stronger than that of the traditional composite box girder and closely relates to the load distribution. Hence, the proposed method further lays the foundation for the analysis and design of CW-SBS box girders.